Russian Women’s Literature of the 18th–19th Centuries in a Historical and Critical Perspective - Jeleńska, Weronika (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article is devoted to the history and reception of women’s literary works in the 18th and 19th centuries. The history of the development of women’s literature shows that it developed quite ambiguously and in “leaps and bounds”, which is explained by political and cultural changes, especially in the mentality of society. The origins of Russian women’s literature date back to the early 18th century, when Peter I fought for the europeanization and cultural development of the whole country. Real change occurred only during the reign of Catherine the Great, who promoted the role of women in literature by being herself a writer. However, prevailing beliefs about the duties and role of women in society prevented them from occupying a prominent place in Russian literature. The position of women writers began to change at the beginning of the 19th century, when women were allowed a place in literary activities and the concept of women’s literature was ﬁrst recognized. The 19th century brought Russian women writers new spaces for creative development and was marked by the ﬁrst attempts to ﬁght for their rights (including through writing). Nevertheless, criticism of women’s literature, which was controlled by men, was still not favorable.